Innovation as A Socio-Technical Transition: The Case of Digital Transportation Service Platforms in Indonesia - Emmanuel, Josephine; Retno, Herni Widya; Yuliar, Sonny (STI Policy and Management Journal, 2023)
The advancement of information and communication technology (ICT) has paved the way for the emergence of digital transportation service platforms worldwide. The emergence of this digital-based innovation in transportation service has triggered debates regarding its legal frameworks. However, digital transportation services have evolved vastly over time and significantly changed urban socio-economic life. The present paper aims to describe the evolution of digital transportation service platforms in Indonesia from the perspective of socio-technical transition developed by Frank Geels and his co-workers. The data used in the paper were obtained from interviews with various actors, field observations, reviews of relevant legal documents, and information from popular media. The results of this study reveal that the transition toward digital transportation services in Indonesia followed a dynamic path in which actors from the government levels, from business sectors as well from local and traditional communities, took part via contested interactions. Understanding this dynamic transition helps in making assessments and planning to achieve sustainability of digital innovation in Indonesia.